Development of Student Worksheets Based on Discovery Learning Assisted by PhET Interactive Simulations - Hajar, Siti; Lasmono S, Paulus G. D.; Purnama, Umi; Silaban, Adeline; Virman (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study aims to design and develop Student Worksheets based on a discovery learning approach, supported by PhET Interactive Simulations media, and to examine their design, feasibility, and practicality in the context of electricity at the high school level. The LKPD development process follows the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The average obtained from the expert validation results is 87.50%, based on three assessment aspects, and is declared to be suiTabel for use. Meanwhile, the feasibility validation by media experts yields an average value of 79.68% across four indikators, indicating that the LKPD is ideal for use. Furthermore, the results of the field trial conducted by students are 82.84%, which is also classified as very appropriate. Based on the average value, it can be said that the physics LKPD based on discovery learning, supported by PhET.